"White" Self-Identification: A Source of Uniqueness Threat. Issue 2 (March 2022) - Rios, Kimberly; Mackey, Cameron D.
The present research introduces the possibility that Whiteness can threaten majority group members' sense of uniqueness and reduce their support for multiculturalism, an ideology that emphasizes recognition of distinctive cultural identities and is seen as primarily relevant to racial/ethnic minorities. Across three studies, being induced to self-identify as "White" (vs. "European American") led majority group members high, but not low, in need for uniqueness (measured in Study 1, manipulated in Studies 2 and 3) to express less positivity toward multiculturalism. Further, the effect of uniqueness motives on reduced support for multiculturalism among participants self-identifying as "White" was mediated by reduced personal feelings of diversity (Study 3). Implications for optimal distinctiveness theory and the functions of White identity are discussed.